NEONATAL HYDROMETROCOLPOS: CLINICAL PRESENTATION AND THERAPEUTIC APPROACH - Dhillon, Rubaid Azhar; Hussain, Ijaz; Qamar, Mohammad Aadil; Ahmed , Saeed; Usman, Muhammad; Fayyaz, Saima; Mirza, Adnan (Journal of Ayub Medical College Abbottabad, 2024)
Hydrometrocolpos (HMC) is a rare pediatric condition characterized by significant enlargement of the uterus and vagina due to the accumulation of fluid, generally caused by a blockage in the lower vagina. This disorder typically presents in newborns with the retention of normal genital tract secretions. The following case report highlights the clinical features, diagnostic process, and treatment of HMC in a newborn. A 3-day-old female presented to the emergency with dehydration, inability to pass stool, and feeding difficulties. Upon physical examination, dehydration and abdominal distention was observed. Initial treatments included hydration and antibiotics. Further investigations confirmed hydrocolpos, leading to an HMC diagnosis due to a congenital blockage in the reproductive tract. A pigtail catheter was used to drained 20ml fluid from the uterus and vagina. Significant clinical improvement as observed. After careful monitoring and treatment, including fluid management and nutritional support, the neonate was discharged on a full oral feed regimen, with plans for long-term nephrology follow-up. Conclusions: Early recognition of HMC is essential to prevent critical complications such as urinary obstruction, renal impairment, and potential rupture of the HMC. The clinical manifestations of HMC correlate with the degree of pressure exerted on adjacent organs, commonly causing hydronephrosis and abdominal swelling.